Influence of Body Position on Intraocular Pressure After Descemet Membrane Endothelial Keratoplasty: A Prospective Randomized Trial. Issue 3 (4th March 2023) - Händel, Alexander; Siebelmann, Sebastian; Lüke, Jan Niklas; Matthaei, Mario; Cursiefen, Claus; Bachmann, Björn
Abstract : Purpose: The purpose of this study was to analyze the influence of patient positioning on intraocular pressure (IOP) after Descemet membrane endothelial keratoplasty (DMEK) in pseudophakic patients treated for Fuchs endothelial corneal dystrophy. Methods: Forty patients were included in this prospective, single-blinded, randomized controlled clinical trial. Patients received a YAG iridotomy 1 day before surgery and an 80% anterior chamber tamponade [20% concentration of sulfur hexafluoride (SF6)]. Postoperative positioning was either supine (group 1) or seated (group 2, at least 30 degrees upper-body high position). IOP was measured with iCare. Results: There was no statistically significant difference in IOP postoperatively [group 1 vs. group 2—after 1h: 13.9 mm Hg (±4.2 mm Hg) versus 13.6 mm Hg (±4.1 mm Hg) ( P = 1.00); after 2h: 13.9 mm Hg (±5.4 mm Hg) versus 15.3 mm Hg (±4.6 mm Hg) ( P = 0.370); after 4h: 13.8 mm Hg (±4.2 mm Hg) versus 15.2 mm Hg (±4.2 mm Hg) ( P = 0.401]. In group 1, 10% of patients showed IOP decompensations well above 30 mm Hg, and in group 2, there were no IOP decompensations. Seated position led to relative risk reduction of 100% and absolute risk reduction of 10% regarding IOP decompensations. The number of patients needed to position seated to prevent 1 additional IOP decompensation was 10. Rebubbling rates, best spectacle–corrected visual acuity, and reduction of corneal thickness were comparable between the 2 groups in the follow-up period up to 1 month. Conclusions: After DMEK in pseudophakic eyes with 80% anterior chamber tamponade, positioning patients with at least 30 degrees elevation of the upper body up immediately after surgery until bedtime prevents IOP decompensations.